Using articulate storyline to enhance student learning engagement in Islamic education - Hamidatusyarifah, Umi; Putri, Sabrina Faradian; Fauziah, Sidi’ Abbas Asmaul; Alivi, Justsinta Sindi (Tawazun: Jurnal Pendidikan Islam, 2026)
This classroom action research aimed to examine the effectiveness of Articulate Storyline–based learning media in enhancing students’ learning activeness in Islamic Education at a vocational high school. The study was conducted in class XI TKJ 1 of SMKN 1 Dlanggu, involving 27 students. The research employed the Kemmis and McTaggart classroom action research model, consisting of planning, action, observation, and reflection, and was implemented in one cycle as the success indicators were achieved. Data were collected through observation sheets of students’ learning activeness and student response questionnaires. The data were analyzed using descriptive qualitative analysis supported by simple quantitative percentages. The results showed a significant improvement in students’ learning activeness, indicated by high percentages across observed aspects, including attention to learning activities, participation in interactive quizzes, responsiveness to teacher questions, and learning enthusiasm. Questionnaire results also revealed that more than 90% of students responded positively to the use of Articulate Storyline, stating that the media made learning more engaging and easier to understand. These findings indicate that Articulate Storyline is effective in fostering active learning in Islamic Education and can serve as an innovative digital learning alternative for vocational high schools. Abstrak Penelitian tindakan kelas ini bertujuan untuk mengetahui efektivitas penggunaan media pembelajaran berbasis Articulate Storyline dalam meningkatkan keaktifan belajar siswa pada mata pelajaran Pendidikan Agama Islam di sekolah menengah kejuruan. Penelitian dilaksanakan di kelas XI TKJ 1 SMKN 1 Dlanggu dengan jumlah subjek sebanyak 27 siswa. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas model Kemmis dan McTaggart yang meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi, serta dilaksanakan dalam satu siklus karena indikator keberhasilan telah tercapai. Pengumpulan data dilakukan melalui lembar observasi keaktifan belajar siswa dan angket respon siswa. Analisis data dilakukan secara deskriptif kualitatif yang didukung oleh data kuantitatif berupa persentase. Hasil penelitian menunjukkan bahwa penerapan media Articulate Storyline mampu meningkatkan keaktifan belajar siswa, yang ditunjukkan melalui meningkatnya perhatian, partisipasi dalam kuis interaktif, respon terhadap pertanyaan guru, serta antusiasme belajar. Respon siswa terhadap penggunaan media juga menunjukkan kategori sangat positif. Dengan demikian, penggunaan Articulate Storyline terbukti efektif dalam meningkatkan keaktifan belajar Pendidikan Agama Islam dan dapat dijadikan alternatif inovasi pembelajaran berbasis teknologi di SMK.